Exploring the relationships between L2 vocabulary knowledge, lexical segmentation, and L2 listening comprehension - Lange, Kriss; Matthews, Joshua (Studies in Second Language Learning and Teaching, 2020)
The capacity to perceive and meaningfully process foreign or second language (L2) words from the aural modality is a fundamentally important aspect of successful L2 listening. Despite this, the relationships between L2 listening and learners’ capacity to process aural input at the lexical level has received relatively little research focus. This study explores the relationships between measures of aural vocabulary, lexical segmentation and two measures of L2 listening comprehension (i.e., TOEIC & Eiken Pre-2) among a cohort of 130 tertiary level English as a foreign language (EFL) Japanese learners. Multiple regression modelling indicated that in combination, aural knowledge of vocabulary at the first 1,000-word level and lexical segmentation ability could predict 34% and 38% of total variance observed in TOEIC listening and Eiken Pre-2 listening scores respectively. The findings are used to provide some preliminary recommendations for building the capacity of EFL learners to process aural input at the lexical level.